The Factors Influencing the Usage of Mobile Commerce among Rural Entrepreneurs in Peninsular Malaysia - Nur Syafiqah A.Samad (International Association of Online Engineering (IAOE), 2021)
This study investigates the factors contributing to the mobile commerce usage among rural entrepreneurs in Peninsular Malaysia. By using the Unified Theory of Acceptance and Use of Technology (UTAUT), the relationship between performance expectancy, effort expectancy, social influence and facilitating conditions on the utilization of mobile commerce were examined. Face to face survey method was used for data collection. 360 samples were subsequently analysed using the Partial Least Square-Structural Equation Modelling (PLS- SEM) method. The study found that social influence was the most influential factor in mobile commerce utilization. The performance expectancy, effort expectancy, social influence, and facilitating conditions were positive and significantly influenced the use of mobile commerce among rural entrepreneurs in Peninsular Malaysia. The findings were added significantly in bridging the knowledge gap concerning the elements influencing the mobile commerce usage among rural entrepreneurs. This empirical study provides significant input to all stakeholders, including government, relevant stakeholders (e.g. entrepreneurs, supply chain industry, telecommunications industry, and ICT industry), and local communities.